Assessment on Seedling Traits of Black Gram (Vigna mungo L. Hepper) Mutants Raised during M2 Generation - Nayak, Bhattu Rajesh; Naik, K. Srinivas; Padiya, Raju; Yugandhar, A.; Kumar, G. Vijay (International Journal of Economic Plants, 2023)
The present study was conducted at department of Genetics, Osmania University, Hyderabad, Telangana, India, during September to November, 2021 with the blackgram accession- IC-436524 obtained from NBPGR regional centre, Hyderabad, Telangana, India and the check T9 was collected from ICAR-CRIDA Hyderabad. The present study aimed to estimate the mutagenic sensitivity of black gram accession- IC-436524 with Ethyl methane sulfonate. Accordingly, this study checked whether the mutagenic activity has been inherited to the next generation M2. Data analysis has been performed for the determination of significance in germination percentage, seedling length (cm), seedling vigor index, root length (cm) and seed survival rate (Day 1 to Day 15) that were observed to be highly significant (p<0.01) for above characters except root length (cm) for treatments. It clearly indicated that there was adequate amount of variability among the black gram mutant due to treatments. The collected data for 7th day observed that seed germination percentage was higher at 0.2% and 0.3% EMS treated mutants and lowest germination percentage was observed in 0.5% EMS treated mutants. Seedling length (cm) was recorded highest in 0.2% EMS treated mutants and lowest seedling length (cm) was recorded in control. Maximum seedling vigor index was recorded in 0.2% EMS treated mutants and lowest seedling vigor index was showed for 0.5% EMS treated mutants. Seedling survival rate data was recorded for 15th day showed higher in 0.2% EMS treated mutants. Data showed EMS has induced mutations during M1 generation and inherited to offspring (M2 generation).